Justicia penal juvenil y reinserción social en el Ecuador. - Velástegui Coloma, Omayra Vanessa (2023)
The purpose of this work is to study the principles and rights that assist adolescents when, due to their behavior, they must be subjected to the administration of criminal justice. The causes why some may commit crimes and the state's response to these behaviors have been investigated; We must take into account that children and adolescents are within the priority attention groups according to the Constitution of Ecuador. Given that there is an increase in delinquent behaviors in adolescents, this work has focused on determining the causes that cause these practices, also criticizing the systems that lead us to witness these behaviors. We must not forget that society and the family are responsible for the acts committed by its citizens, when they are not given adequate living conditions for their development. Finally, the measures that are applied for the treatment of young people within what is considered restorative criminal justice and the effectiveness of these measures according to the justice operators in the matter are addressed.